Perbandingan Kinerja Keuangan PT. Bank SeaBank Sebelum dan Sesudah Akuisisi: Studi Literatur - Ramadhani, Nur Fitri; Yuliana, Yuliana; Dhafyah, Athaya Aqilah; Wulandari, Wulandari (Universitas Dharmawangsa, 2025)
This study analyzes the financial performance of PT. SeaBank before and after the acquisition by Sea Group, with a focus on digitalization. Using the quantitative approach and Wilcoxon test method, the study found that the increased significantly, while the Capital Adequacy Ratio (CAR) remained stable. Although operational efficiency as measured by Operating Expenses to Operating Income (BOPO) shows improvement, Return on Assets (ROA) remains negative, reflecting challenges in profitability. These results highlight that although acquisitions have a positive impact on credit disbursement efficiency, there is still a need to improve profit performance. This research provides important insights into the impact of acquisitions in the digital banking sector in Indonesia, as well as demonstrating the need for better risk management to ensure the continued growth and financial health of banks in the future.